Differences in Caries Severity Based on Sociodemographic Factors in Pediatric Patients at Universitas Brawijaya Hospital - Edina Hartami,; Yuanita Lely Rachmawati,; Ambar Puspitasari,; Amirah Nanda Herlambang, (Dentika: Dental Journal, 2024)
Early childhood caries (ECC) is influenced by age and gender, with the severity of primary dental cavities being measured using dmf-t index. Therefore, this research aimed to identify differences in caries severity based on age and gender among pediatric patients at Universitas Brawijaya Hospital. The identification process was conducted through an analytical observational method using secondary data, comprising 71 medical records of pediatric patients receiving treatment in the hospital from April 2021 to November 2022. Medical records were observed by examining the number of teeth with decay, missing, and filling, as well as age and gender. According to the chi-square test results, there were no significant differences in caries severity based on age or gender (p > 0.05). In conclusion, this research showed no differences in caries severity based on sociodemographic factors in pediatric patients.